Deskripsi Strategi Guru Menanamkan Profil Pelajar Pancasila SDN 17 Pontianak Kota - Lansan, Dominikus Irawan; Kresnadi, Hery; Pranata, Rio (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study aims to describe the teacher's strategy to instill a student's Pancasila learner profile carried out in class. The research method uses descriptive qualitative research type of case study and data collection techniques through interviews, observation and documentation. The results showed that the implementation of the class teacher's strategy in instilling the profile of Pancasila students in class IV A has been carried out by teachers through several strategies that have been implemented such as (1) The teacher's strategy to instill the profile of Pancasila students in the dimensions of faith, piety to God Almighty and noble character by teaching students to apply religious values at school, behaving positively as a role model for students. (2) The teacher's strategy to instill the global diversity dimension of the Pancasila learner profile by providing an understanding of the cultures that exist in Indonesia, applying tolerance. (3) The teacher's strategy to instill the profile of Pancasila students in the dimension of mutual cooperation by increasing students' cooperation skills. (4) The teacher's strategy to instill an independent dimension of the Pancasila learner profile by providing tasks that must be done by students themselves. (5) The teacher's strategy to instill the profile of Pancasila learners in the dimension of critical reasoning by involving students in open discussions. (6) The teacher's strategy instills the creative dimension by giving art or craft project assignments. Obstacles contained in the application of class IV A strategies to instill the profile of Pancasila learners.